Social Robotics 5th International Conference, ICSR 2013, Bristol, UK, October 27-29, 2013, Proceedings - Herrmann, Guido; Pearson, Martin; Lenz, Alexander; Bremner, Paul; Spiers, Adam; Leonards, Ute (Lecture Notes in Artificial Intelligence, 2013)
This book constitutes the refereed proceedings of the 5th International Conference on Social Robotics, ICSR 2013, held in Bristol, UK, in October 2013. The 55 revised full papers and 13 abstracts were carefully reviewed and selected from 108 submissions and are presented together with one invited paper. The papers cover topics such as human-robot interaction, child development and care for the elderly, as well as technical issues underlying social robotics: visual attention and processing, motor control and learning.